THE CORRELATION BETWEEN TRANSLATION ABILITY AND READING HABIT TOWARD READING SKILL - nur arqom eka fatria (Language-Edu, 2020)
AbstractThe purpose of this research is to identify the connection between the ability to interpret and learn, the ability to read and read, the ability to translate and the tendency to read and read. This is a correlational method of research that is a form of quantitative research. The population of the study is the students’ fifth semester in UNU Blitar. The sample are 52 students. Test and questionnaire are the methods used to collect the data. The test collects translation and reading data, whereas the questionnaire is used to know the reading pattern of students. The results of this research reveal that 1) the correlation between interpreting and reading is positive. (rxly=4.85); 2) there is a positive correlation between reading habit and reading skill (rx2y=2.32); and 3) there is a positive correlation among translation ability, reading habit and reading skill (R = 0.497). The results of this research indicate that the ability to interpret and read behaviors relate in particular to the students' ability to read and address the question of the tests. Language skills and comprehension practice should also be applied in teaching and comprehension learning. A teacher of English has to organize certain activities in his curriculum that increase the ability to read and to read habits related to teaching.Keywords: Translation Ability, Reading Habit, Reading Skill